2017
DOI: 10.1016/j.icarus.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Reversal and amplification of zonal flows by boundary enforced thermal wind

Abstract: Zonal flows in rapidly-rotating celestial objects such as the Sun, gas or ice giants form in a variety of surface patterns and amplitudes. Whereas the differential rotation on the Sun, Jupiter and Saturn features a super-rotating equatorial region, the ice giants, Neptune and Uranus harbour an equatorial jet slower than the planetary rotation. Global numerical models covering the optically thick, deep-reaching and rapidly rotating convective envelopes of gas giants reproduce successfully the prograde jet at th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Dietrich et al. 2017), and we also find this to be the case in our simulations. While this advection term may be important for transporting angular momentum (McIntyre 1998; Miesch & Hindman 2011), it cannot play a role in setting the amplitude of the time-averaged (steady) zonal flow.…”
Section: Theorysupporting
confidence: 90%
See 1 more Smart Citation
“…Dietrich et al. 2017), and we also find this to be the case in our simulations. While this advection term may be important for transporting angular momentum (McIntyre 1998; Miesch & Hindman 2011), it cannot play a role in setting the amplitude of the time-averaged (steady) zonal flow.…”
Section: Theorysupporting
confidence: 90%
“…Averaging (3.11) along the axial direction and in time leaves only the two advective terms and the viscous term. For a careful derivation of the balance between the averaged advection term and the viscous term in spherical coordinates, see Dietrich, Gastine & Wicht (2017). Previous studies have found that the mean-mean term is small (e.g.…”
Section: Theorymentioning
confidence: 99%
“…Thus, the constant of integration is specified by requiring the z-average of U tw to be zero. Numerical simulations by Dietrich et al (2017) demonstrated that this is indeed the case (see their Figure 4).…”
Section: Model Of Convection and Zonal Circulationmentioning
confidence: 75%
“…These studies have employed a variety of techniques including Direct Numerical Simulation (DNS) [9,10], turbulence closure models [11,12] or Direct Statistical Simulation (DSS) [13][14][15]. Investigations have been performed in both spherical geometry [9,[16][17][18][19][20][21][22][23][24] and in local Cartesian models [25][26][27][28][29][30][31]. There is also a class of intermediate local models that captures some of the effects of the vortex stretching engendered by the spherical geometry by use of an annulus geometry [32][33][34].…”
Section: Introductionmentioning
confidence: 99%